User experience-enhanced and energy-efficient task scheduling on heterogeneous multi-core mobile systems - Huang, Yanting (2020)
Heterogeneous Multi-Core Mobile Systems has been widely used to improve performance. However, it faces with the challenge of tradeoff between energy saving and user experience. ARM big. LITTLE architecture, a heterogeneous computing architecture, is a power-optimization technology. In most big. LITTLE devices, however, it still cannot achieve excellent user experience and higher energy saving. In this paper, we propose an improved task scheduling (UCES-GTS) by introducing the concept of user-centric task on big. LITTLE mobile device. In order to enhance user experience, the response time of user-centric tasks is shortened with reducing slack time of them properly. We then present a detailed algorithm to compute appropriate frequency and allocate the CPU resources to each task. The experimental evaluation results show that our improved global task scheduling model can achieve 17 % and 8 % energy saving average compared with the clustered switching scheduling and the original global task scheduling respectively. And the response time of user-centric tasks can decrease 27 % average, which means excellent user experience.